Microbial carbon oxidation in seawater below the hypoxic threshold - Sarah Wolf; Clare Jayawickrama; Craig A. Carlson; Curtis Deutsch; Edward W. Davis; Benjamin N. Daniels; Francis Chan; Stephen J. Giovannoni (Scientific Reports)
Abstract Global oxygen minimum zones (OMZs) often reach hypoxia but seldom reach anoxia. Recently it was reported that Michaelis Menten constants (Km) of oxidative enzymes are orders of magnitude higher than respiratory Km values, and in the Hypoxic Barrier Hypothesis it was proposed that, in ecosystems experiencing falling oxygen, oxygenase enzyme activities become oxygen-limited long before respiration. We conducted a mesocosm experiment with a phytoplankton bloom as an organic carbon source and controlled dissolved oxygen (DO) concentrations in the dark to determine whether hypoxia slows carbon oxidation and oxygen decline. Total oxygen utilization (TOU) in hypoxic treatment (ca. 7.1 µM O2) was 21.7% lower than the oxic treatment (ca. 245.1 µM O2) over the first 43 days of the experiment. In addition, following the restoration of fully oxic conditions to the hypoxic treatment, TOU accelerated, demonstrating that oxidative processes are sensitive to DO concentrations found in large volumes of the ocean. Microbial amplicon-based community composition diverged between oxic treatments, indicating a specialized microbiome that included Thioglobaceae (SUP05 Gammaproteobacteria), OM190 (Planctomycetota), ABY1 (Patescibacteria), and SAR86 subclade D2472, thrived in the hypoxic treatment, while the genus Candidatus Actinomarina and SAR11 alphaproteobacteria were sharply inhibited. Our findings support the hypothesis that oxygenase kinetics might slow the progression of ocean deoxygenation in oxygen-poor regions and be a factor in the evolution of microbial taxa adapted to hypoxic environments.